Decision Support System for Eucalypt Plantation Investment in Chachoengsao Province - Diloksumpun, Piyawat (วารสารวนศาสตร์ไทย, 2022)
The present study was aimed to develop an integrated decision support system (DSS) for eucalypt plantation investment in Chachoengsao province that could be able to determine site suitability, plantation yield, appropriate plantation management, and economical profits. To meet all objectives of the present study, the DSS development can be separated into 4 main parts including database design and analysis, DSS procedure, user interface design and system output. Firstly, a system database was designed and developed to provide critical requirements for decision making based on the DSS objectives. Secondly, decision hierarchy was constructed to clarify the choice situation of user-defined areas accordingly. Based on economic production of the 3-year rotation, site suitability was classified into 4 classes, i.e. very good, good, moderate and unsuitable sites. Yield estimation of eucalypt plantation was analyzed to provide information for financial analysis procedure. Thirdly, the user interface management system was designed according to the user-friendly interactive concept for simplicity and high information content. The welcome homepage, input data page, interactive pages and output page were then designed to communicate with users step by step. Lastly, summary report output page was designed to briefly provide all information needed for decision making of eucalypt plantation investment. Furthermore, the DSS developed in the present study was designed to be flexible and could be updated some system database for future uses and development. Development of a growth model that integrated site potential, climatic data and physiological characteristics as well as management practices is, therefore, essential to improve the accuracy of the growth/yield prediction in decision making. Keywords: Decision support system, Eucalypt plantation, Site suitability, Chachoengsao